A View on Education, Life and Attitudinal Aspects for Violence in Arab Sector of Israel - Adelina STEFARTA; Eman AYOUB (Eastern European Journal of Regional Studies)
Violence provides its presence in a wide spectrum of everyday life. In these days we are witnesses of violence in high levels. Problems are not solved, and that gives us a look to that life accompanied with torture and suffering, although that logic leads a person that suffer to try to change their realty but that’s mostly do not happens. It is clearly seen that family violence cases and couples difficult situation lead to a continuous suffering and daily violence. This research describes people’s attitude for violence of Arab Sector of Israel.